Stugdy of steel roof and wall-cliding sheet metals and computer-aided drafting / Walter Andrew Maurice, Azmie Jumit and Victor Glance Tiongin - Maurice, Walter Andrew; Jumit, Azmie; Tiongin, Victor Glance (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 1996)
Roofing have played an important part in the process of making buildings nowadays . roof are designed with specifications to suit buildings , its' comfortness and it is designed specially with unigueness to satisfy customers . Yet , the roof most important role is to give protection to buildings . Roofing materials is usually made from different varieties of metals such as Steels , Aluminium and Zinc which some are being coated by different materials to improve its' condition and longlastivity . Here are some of the examples of different kind of roof made by different manufacturers all around the world .